A case study on identifying the aesthetic values of lower limb prosthetic / Ong Sze Xian and Indera Irawan - Ong, Sze Xian; Irawan, Indera (2019)
Prosthesis refers to the artificial extension or equipment that substitutes a missing body part, be it an eye, a nose, a tooth, a facial bone, and even upper or lower body limbs. Aesthetic denotes the value of a property based on its appearance. Application of aesthetic values on prosthesis design adds to its attraction that enhances positivity and increases the psychological acceptance of the "new limb". Nevertheless, investigations that focused on this particular subject matter are in scarcity, especially those that analysed the correlation between aesthetic attraction to devices and their human-likeness. As such, this study conducted a literature review analysis and several semi-structured interview sessions with selected lower limb prosthesis users. The primary objective of this study was to determine the level of aesthetic satisfaction amongst selected local prosthesis users regarding their prosthetic devices. As a result, the study outcomes displayed that males were more satisfied with their prosthesis than the females did. In comparison to the female respondents, the males exerted higher tendency in wearing cosmesis. Apart from that, an amputee who resided at the urban area seemed to be more willingly to wear artificial limb than those who lived in small town. Amputees with lower physical activity level were more likely to choose prosthesis that resembled the normal human limb embedded with realistic details, such as toes and skin colour. Therefore, the study yields bridge the gap in information and add to the existing knowledge concerning aesthetics of prosthesis design, apart from encouraging enhancements for future prosthesis design.